Emergently Alteration of Procedural Strategy During Transcatheter Aortic Valve Replacement to Prevent Coronary Occlusion: A Case Report - Dai, Hanyi; Zhou, Dao; Fan, Jiaqi; Wang, Lihan; Yidilisi, Abuduwufuer; Zhu, Gangjie; Jiang, Jubo; Li, Huajun; Liu, Xianbao; Wang, Jian’an (Frontiers in Cardiovascular Medicine, 2022)
Background Coronary occlusion is an uncommon but fatal complication of transcatheter aortic valve replacement (TAVR) with poor prognosis. Case presentation A patient with symptomatic severe bicuspid aortic valve stenosis was admitted to a high-volume center specializing for transfemoral TAVR with self-expanding valves. No anatomical risk factors of coronary occlusion were identified on pre-procedural computed tomography analysis. The patient was scheduled for a transfemoral TAVR with a self-expanding valve. Balloon pre-dilatation prior to prosthesis implantation was routinely used for assessing supra-annular structure and assessing the risk of coronary occlusion. Immediately after the tubular balloon inflation, fluoroscopy revealed that the right coronary artery was not visible, and the flow in left coronary artery reduced. The patient would be at high-risk of coronary occlusion if a long stent self-expanding valve was implanted. Therefore, our heart team decided to suspend the ongoing procedure. A transapical TAVR with a 23 mm J-valve was performed three days later. The prosthesis was deployed at a proper position without blocking the coronary ostia and the final fluoroscopy showed normal flow in bilateral coronary arteries with the same filling as preoperatively. Discussion Our successful case highlights the importance of comprehensive assessment of coronary risk and thorough understanding about the TAVR procedure for the heart team. A short-stent prosthesis is feasible for patients at high risk of coronary occlusion. Most importantly, when an extremely high risk of coronary obstruction is identified during procedure and no solution can be found, TAVR should be called off even if the catheter has been introduced.